An Unusual Presentation of a Large Calcified Thyroid Nodule. (7th November 2018) - Jayarajah, Umesh; Wijerathne, Pradeep; Basnayake, Oshan; Seneviratne, Sanjeewa
Abstract : This case highlights the rare occurrence of a large benign calcified nodule of the left lobe of the thyroid gland with associated obstructive symptoms. Unusually, the calcification was confluent with similar calcified nodules in the subcutaneous tissue plane. The symptoms were alleviated following a total thyroidectomy.